Interfacial Polarization Loss Improvement Induced by the Hollow Engineering of Necklace‐like PAN/Carbon Nanofibers for Boosted Microwave Absorption - Xiao, Junxiong; Zhan, Beibei; He, Mukun; Qi, Xiaosi; Gong, Xiu; Yang, Jing‐Liang; Qu, Yunpeng; Ding, Junfei; Zhong, Wei; Gu, Junwei (Advanced functional materials, 2025)
Rational manipulation of composition and microstructure design is recognized as an effective pathway to realize multifunctional high‐performance microwave absorber. In this work, necklace‐like hollow polyacrylonitrile (PAN)/carbon nanofibers are designed and constructed through a simple continuous electrospinning‐carbonization‐etching route. Specifically, by varying the carbonization temperature, the ratio of PAN to carbon content of necklace‐like hollow PAN/carbon nanofibers can be effectively regulated, resulting in tunable electromagnetic parameters and conductive loss capacities. After that, the hollow structure is further introduced to improve the feature of lightweight, impedance‐matching characteristics, and interfacial polarization loss ability. Accordingly, the necklace‐like hollow PAN/carbon nanofibers exhibited a frequency bandwidth of 6.60 GHz and a minimum reflection loss of −44.73 dB at 1.76 mm. Both the experimental and theoretical simulation results indicated that the obtained necklace‐like hollow PAN/carbon nanofibers possessed the high chemical stability and excellent microwave absorbing performance, endowing them as the excellent candidates for microwave absorbers in the extreme conditions. Therefore, the findings not only offered a simple pathway to rationally manipulate composition and microstructure but also provided a novel technique to make the most of hollow engineering for strengthening interface polarization loss. Hollow engineering is adopted to design necklace‐like hollow PAN/carbon nanofibers for their boosted impedance matching characteristics, interfacial polarization loss ability, and comprehensive microwave absorption properties. The high chemical stability of PAN and carbon endows corrosion resistance, and the introduction of hollow structure further contributes to feature of lightweight.